Young People between Traditional Media and New Media - بوعلي, نصير صالح (ALBAHITH ALALAMI, 2015)
This Research based on an empirical study and tested the hypothesis of transition effects on a sample of young people in Sharjah University and trying to identify a new form of Media which is based on the production of new types of habits and patterns and their cultural impact. Recently, New Media appeared to refer to new types of Communication using the Internet. It’s enormous in the exchange of Information. The new Media contains multiple forms, including the form in which users produce by them to refer the entry of a new area of Media in which exchange of roles between the Sender and the recipient. This study is trying to identify a new form of Media Web used (Press online or only Press online, Digital Radio and the Web-Sat) and to compare these with Traditional Media (Newspapers, Classic Radio and the Analogical TV). Why the University Students like, the Traditional Media or the new Media? In conclusion, New Media is the main actor which constructs specific concepts relating to identifying. Most of the time Universities Students Used for the famous Media such as Digital TV or Media Interactivity. This is influenced by the latest on the educational achievement of students.